Currículo por competências : recontextualizações em um curso técnico da educação profissional - Lima, Tatiana Michelli de (2013)
This research investigates the recontextualization of the curriculum by powers, having as the locus of research to Professional Education. As regards the delineation of space/time, this research occurred between the years 2009 and 2010, in technical course of Safety in the workplace, in the unity of teaching SENAI-Cuiabá. The choice of this educational institution she was be the Professional Education and the largest unit of teaching researched. In institution with regard to the methodology, is embodied by a qualitative approach to nature descriptive and interpretative. The general objective was to understand the recontextualization of the subjects in relation to this curriculum. Specific objectives were: identify, relate to and understand the positions on the competency curriculum to analyze and understand the documents of the institution researched, in global scope, national and local; analyze and relate the contexts of the cycle of policies in competency curriculum. Was held, bibliographical study, documentary study and semi-structured interviews with the subjects. In the analysis of documents and semi-structured interviews focused approach of theoretical/methodological Cycle of policies proposed by Ball (2009, 2011), to understand the contexts of influence the production of text and practice, in the research institution, In search of this understanding, in theoretical terms, the research was based by Ball (2009, 2011), Lopes (2008), Macedo (2002), Mainardes and collaborators (2011), and Oliveira (2009) by working with Policy of Curriculum; Lopes and Macedo (2011), to work with Curriculum; and Deluiz (2007), Lopes (2008), Macedo (2002), Medeiros (2012) and Perrenoud (1999), by working with competency curriculum; and seek Bernstein (2003); Medeiros (2012), Perrenoud (1999) and Rios (2011) and Ramos (2011) by working with notions of competence. The study has observed that, in the context of influence, the influence of social actors in global scope on the official texts on a national level. In the context of the production of the text, we observed dry the curriculum of research institution, was recontextualized by social actors, who drew up the plan of technical course Work Safety; and that demand of economic policy is still influencing the production of text. In the context of the practice, it was analyzed the recontextualized of social actors, who were understood by means of semi-structured interviews. It was observed that social actors recontextualizes the competency curriculum, with its daily practices in the unit teaching SENAI-Cuiabá.